2017
DOI: 10.3389/fmicb.2017.01141
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mass and Diversity of the Colonic Microbiome in Patients with Multiple Sclerosis and Their Improvement with Ketogenic Diet

Abstract: Background: Colonic microbiome is thought to be involved in auto-immune multiple sclerosis (MS). Interactions between diet and the colonic microbiome in MS are unknown.Methods: We compared the composition of the colonic microbiota quantitatively in 25 MS patients and 14 healthy controls.Fluorescence in situ hybridization (FISH) with 162 ribosomal RNA derived bacterial FISH probes was used. Ten of the MS patients received a ketogenic diet for 6 months. Changes in concentrations of 35 numerically substantial bac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 17 publications
4
114
0
2
Order By: Relevance
“…Conversely, some human studies that examined ketogenic diets suggest negative impacts on microbial ecology and gut health. However, these studies were conducted in small cohorts with specific metabolic conditions (60,61), limiting generalization to larger populations. Because modified versions of ketogenic diets are rapidly growing in popularity, it is necessary to examine their long-term safety and impacts on the gut microbiota and intestinal environment.…”
Section: Ketogenic Dietmentioning
confidence: 99%
“…Conversely, some human studies that examined ketogenic diets suggest negative impacts on microbial ecology and gut health. However, these studies were conducted in small cohorts with specific metabolic conditions (60,61), limiting generalization to larger populations. Because modified versions of ketogenic diets are rapidly growing in popularity, it is necessary to examine their long-term safety and impacts on the gut microbiota and intestinal environment.…”
Section: Ketogenic Dietmentioning
confidence: 99%
“…The authors concluded that the KD is safe, feasible with 90% compliance, and potentially effective as the KD cohort displayed clinically meaningful improvements in health-related quality of life (HRQOL) summary scale scores as well as a mild reduction in expanded disability scale status [137]. Recent clinical evidence suggests that the impaired colonic microbiome function observed in patients with multiple sclerosis is normalized by 6 months of ketogenic diet therapy; however, as no specific microbiome pattern was apparent and shifts in bacterial populations were multidirectional, the precise role for microbiome changes in MS pathology remains unclear [138]. Further clinical studies including imaging outcomes, blinded clinical trials, and immune assays are warranted to better define KD efficacy in these conditions.…”
Section: Other Neurologic Disordersmentioning
confidence: 99%
“…Various approaches have focused on studying the intestinal microbiota either by quantitative techniques of microorganism culture [9] or by quantifying 16s rRNA fragment as a marker-gene. Marker-gene techniques include denaturing gradient gel electrophoresis (DGGE) [19], terminal restriction fragment length polymorphism (T-RFLP) [20], quantitative PCR (qPCR) [21], fluorescence in situ hybridization (FISH) [22] or plasmid-clone capillary Sanger sequencing [23]. However, for complex and diverse ecosystems such as intestinal microbiota, the previously mentioned methods have provided incomplete profiles of microbial community structure.…”
Section: Introductionmentioning
confidence: 99%